Asymmetric phase-transfer catalysed β-addition of isoxazolidin-5-ones to MBH carbonates. Issue 22 (18th October 2018) - Capaccio, Vito; Zielke, Katharina; Eitzinger, Andreas; Massa, Antonio; Palombi, Laura; Faust, Kirill; Waser, Mario
Abstract : A novel organocatalytic approach for the asymmetric synthesis of α-allylated highly functionalised β-amino acids was developed. Abstract : A novel high yielding, enantio - and diastereoselective protocol for the synthesis of α-allylated highly functionalised β-amino acid derivatives by adding isoxazolidin-5-ones to MBH carbonates under asymmetric phase-transfer catalysis has been developed.